PERENCANAAN PEMANFAATAN PEMBANGKIT LISTRIK TENAGA ENERGI BARU TERBARUKAN (PLT-EBT) PADA LOKASI WISATA DI DAERAH TERPENCIL - Permana, Ika Dian; Tamaji (Seminar Nasional Ilmu Terapan, 2024)
Indonesia is located in a tropical region and is crossed by the equator, therefore the Indonesian territory will be continuously illuminated by the sun during the day. This is an added value that must be utilized for equitable development in Indonesia. The need for energy throughout Indonesia is sometimes hindered by geographical conditions in the form of mountains and wilderness. Where the PLN electricity network has difficulty reaching remote areas. Meanwhile, remote areas sometimes have tourism potential that can be developed further, such as mountain peaks or hills, waterfalls in the middle of the forest and so on. Utilization of renewable energy can use solar panels, wind turbines or water turbines. This journal uses descriptive research methods that collect data from New Renewable Energy Power Plant (PLT-EBT) system equipment consisting of Solar Power Plants (PLTS), Wind Power Plants (PLTB) and Hydro Power Plants (PLTA) and calculation of electrical energy consumption at simple tourist attractions as input for mathematical simulations